Breaking Bad News in Cancer Care: Ethiopian Patients Want More Information Than What Family and the Public Want Them to Have. (2021) - Abraha Woldemariam, Aynalem; Andersson, Rune; Munthe, Christian; Linderholm, Barbro; Berbyuk Lindström, Nataliya
Abstract : PURPOSE: This study explores the preferences of patients with cancer, family caregivers, and the general public regarding breaking bad news in an Ethiopian oncology setting. METHODS: The study was conducted at Tikur Anbessa (Black Lion) Specialized Hospital. The sample consists of patients with a confirmed cancer diagnosis, their family caregivers, and representatives from the general public with 150 subjects per cohort. The study used a comparative cross-sectional design and multivariable data analysis. RESULTS: The patients would like to be informed, which contradicts the preferences of family caregivers. This creates an ethical dilemma for staff in terms of how much they involve their patients in clinical decision making. The patients also indicate that information should not be withheld from them. By contrast, the general public prefers information about poor life expectancy to be communicated to family only, which may reflect a widespread public perception of cancer as a deadly disease. CONCLUSION: The findings indicate the complexity of communication-related preferences concerning breaking bad news in oncology care in Ethiopia. It requires oncologists to probe patient attitudes before information disclosure to find a balance between involving patients in communication at the same time as keeping a constructive alliance with family caregivers.